ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIKA BERDASARKAN TEORI NEWMAN - Ririn Rahmawati; Fertilia Ikashaum (Hipotenusa Journal of Research Mathematics Education (HJRME), 2021)
Problem solving ability is one of the mathematical abilities that need to be mastered by students to equip students in logical, analytical, systematic thinking and the ability to work well together. In addition, this problem solving ability is very important for students to train students in solving problems in everyday life. This study aims to analyze student errors in solving mathematical problem solving problems based on Newman's theory. The type of research used is descriptive qualitative. The subjects of this study were students of class VII-A SMP Muhammadiyah 1 Menggala. Data collection used in the form of tests, interviews and documentation. The results showed that the most mistakes made by students were in writing the final answer, which was caused because students did not understand the commands in the questions well. The second most common error is the transformation error caused because students do not have the skills to change the language of the problem into a mathematical model. The third error, namely misunderstanding the problem caused by students not being careful in writing down the information in the problem, and not getting used to writing down the information in the problem when solving math problems. The fourth error, namely the error of process skills caused by students not being careful in carrying out the calculation process